Design and simulation of a PWM based phase synchronous inverter for utility grid systems with 20km feeder line - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Hossain, A. K. M. Zakir (UiTM Press for the Institute of Research Management & Innovation (IRMI), Universiti Teknologi MARA (UiTM), 2017)
In recent years, the utility grid system is essential for the power transmission and distribution system because it is reliable, gives low harmonic distortion, has proper phase synchronization and environment-friendly. PWM based phase synchronous invert systems are generally utilized in the high-efficiency energy supply, long distance transmission lines and higher power quality. The inverter output voltage depends on the coupling transformer, input sources, LCL filter and inverter controllers. An inverter based on three level IGBT has been designed for utility grid and simulated by MATLAB2014a. In this paper, the PWM controller is used to generate a pulse signal to control electronic switches and precisely synchronize with grid line frequency. LCL filters are used at both input and output side to suppress the DC ripple current, noise and synchronous the output phase between the inverter and the utility grid. In this system, the input DC voltage is 500V, switching frequency is 1.65 kHz, grid frequency is 50Hz, 20 km feeder with 30MW three phase load and also a balanced utility grid load of star configuration (00 , 1200 , and 2400 degree) has been considered for this design purpose. Results show that the system conversion efficiency is 98.94% with total harmonic distortion (THD) 1.06% in the inverter side and the conversion efficiency is 98.96% with THD 1.04% in the utility grid side.